Pengaruh Budaya Organisasi, Lingkungan Kerja, dan Kompensasi terhadap Kinerja Karyawan Kota Mojokerto - Galuh Yuliana Dewi (JES (Jurnal Ekonomi Syariah), 2021)
Abstract: This research is quantitative research that emphasizes its analysis of numerical data (numbers) processed by statistical methods. The goal is to know if there are influence between organizational culture (X1), work environment (X2), and compensation (X3) of the employees performance in PT. BPRS Mojokerto City. The sample used in this research were 38 employees. From the results of research above can be concluded that there is positive and significant influence partially on cultural organization variables. Variable (X1) on employees performance (Y) in PT. BPRS Mojokerto City is 0.016 > 0.05 and the value of t count > t table is 2,546 > 2,028. Then, from the result test on the working environment variable (X2) against Y is 0.009 < 0.05 and the values of t count is 2.763 > 2.028. There is positive and significant partially effect of variable work environment (X2) of employees performance (Y) in PT. BPRS Mojokerto City. Then, the result of compensation (X3) effect of performance (Y) variable in PT. BPRS Mojokerto City is negatif and not significant partially. The value is 0.826 > 0.05 and t counted 0.221 < t table 2,028. At the f test counted 9,309 so that the f count > f table is 9.309 > 2.87, and the p-value (sig) counted 0.000 > less than 0.05. Thus, organizational cultural variables (X1), work environment (X2), and compensation (X3) have simultaneous effect on employees performance (Y) in PT. BPR Syariah Mojokerto City.